Genetic Diversity Analysis of Cultivated Kappaphycus in Indonesian Seaweed Farms using COI Gene - Ratnawati, Pustika; Simatupang, Nova F; Pong-Masak, Petrus R; Paul, Nicholas A; Zuccarello, Giuseppe C (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2020)
Indonesia is a major player in the aquaculture of red algae, especially carrageenan producing ‘eucheumatoids’ such as Kappaphycus and Eucheuma. However, many current trade names do not reflect the evolutionary species and updated taxonomy, this is especially the case for eucheumatoid seaweeds that are highly variable in morphology and pigmentation. Genetic variation is also not known for the cultivated eucheumatoids in Indonesia. Therefore, this study aimed to determine the species and the level of genetic variation within species of cultivated eucheumatoids from various farms across Indonesia, spanning 150-1500 km, using the DNA barcoding method. Samples of seaweed were randomly collected at 14 farmed locations between April 2017 and May 2018. For this study the 5-prime end ( 600 bp) of the mitochondrial-encoded cytochrome oxidase subunit one (COI) was amplified and sequenced. Morphological examination showed that the samples were quite variable in branching pattern and color. All samples collected from farms with floating line cultivation were identified based on COI sequences as Kappaphycus alvarezii and showed no variation in the COI gene. One farm sample with bottom-line cultivation was identified as K. striatus. The low genetic variation is in contrast to the phenotypic variation of samples, indicating that variation and phenotypic responses to environments is still found in samples with implications for growth rates and carrageenan yield and quality. Information about the genetic variation in stocks is important base knowledge for maintaining, expanding and continuing seaweed aquaculture.